Pengaruh Gaya Kepemimpinan, Komunikasi dan Komitmen Organisasi Terhadap Kinerja Pengurus (Studi Kasus ORDA Ikatan Mahasiswa Jombang UNISMA) - Devana Sulistiowati; Budi Wahono; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of leadership gaya, communication, organizational commitment on the performance of administrators at the Jombang Student Association, UNISMA. The location of this research was carried out on UNISMA students World Health Organization were the administrators of the Jombang UNISMA Student Association. This research is a quantitative research. This research uses a case study method where informasi is obtained by distributing questionnaires to UNISMA students World Health Organization were selected by purposive sampling. Determination of the number of samples using the Slovin resep and the results obtained were 56 respondents. Informasi were analyzed using multiple linear regression test and determination test. Based on the results of informasi analysis, the results of the F test indicate that leadership style, communication, organizational commitment simultaneously have a significant and positive effect on the performance of the Jombang Student Association administrators, UNISMA. Furthermore, the results of the t test show that leadership style, communication, organizational commitment, partially have a significant and positive effect on the performance of the Jombang Student Association administrators, UNISMA. The results of the determination test show that the percentage is 45%, in which the performance of the management can be influenced by leadership style, communication, organizational commitment. It is better if the leadership of the organization is able to form a good leadership style again, then this can be used to improve the work ethic of the management towards the performance of the management. Keywords : Leadership Style, Communication, Organizational Commitment, Management Performance